Catalytic Ozonation of Recalcitrant Organic Chemicals in Water Using Vanadium Oxides Loaded ZSM-5 Zeolites - Xu, Yingying; Wang, Qinghong; Yoza, Brandon A.; Li, Qing X.; Kou, Yue; Tang, Yuqi; Ye, Huangfan; Li, Yiming; Chen, Chunmao (Frontiers in Chemistry, 2019)
The discharge of wastewater having recalcitrant chemical compositions can have significant and adverse environmental effects. The present study investigates the application of a catalytic ozonation treatment for the removal of recalcitrant organic chemicals (ROCs) from the water. Novel catalytic materials using vanadium (V) oxides deposited onto the surface of NaZSM-5 zeolites (V/ZSM) were found to be highly efficient for this purpose. The highly-dispersed V oxides (V4+ and V5+) and Si-OH-Al framework structures were determined to promote the surface reaction and generation of hydroxyl radicals. The constructed V1/ZSM450 (0.7 wt% of V loading and 450 °C of calcination) exhibited the highest activity among the developed catalyst compositions. The V1/ZSM450-COP increased the mineralization rate of nitrobenzene and benzoic acid by 50% and 41% in comparison to single ozonation. This study demonstrates the enhanced potential of V/ZSM catalysts used with COP for the treatment of chemical wastewaters.